Transformation Tradition: Incorporating Technology and Local Culture in Sundanese Script - Agung Zainal Muttakin Raden; Rustopo Rustopo; Timbul Haryono (Cultural Syndrome, 2019)
The Sundanese script has a philosophy of life for the Sundanese people, this script is a system for writing Sundanese. The traditional writing system in Sundanese began in the 14th century to the 19th century. This article will discuss the role of digital technology in creating the Sundanese script, using ATUMICS method, ATUMICS is an acronym for Artifact, Technique, Utility, Material, Icon, Concept and Shape. The ATUMICS approach is carried out to review the transformation of tradition in the Sundanese script. The ancient Sundanese script and the modern Sundanese script will be compared with ATUMICS approach. the results of this study were to determine the change or transformation of tradition in the Sundanese script. Transforming tradition is a way to create a new product derived from traditions, with adjustments to the six elements contained in the ATUMICS theory. Transformation of tradition is an effort to maintain tradition in the modern era which is adjusted to the times.